Relations between speech production, speech perception, and spelling in children with complex communication needs: a preliminary examination. (3rd April 2019) - McCarthy, Jillian H.; Hedrick, Mark; Springer, Cary
ABSTRACT: Purpose: To determine the influence of speech production and speech perception upon spelling abilities in children with complex communication needs (CCN). Methods: Eight children (3 females, 5 males) with cerebral palsy, who did and did not use augmentative and alternative communication (AAC), were recruited to participate. The participants ranged in age from 5 years, 8 months to 11 years, 5 months ( M  = 8 years, 3 months). The children were assessed using clinical tests of speech production (or intelligibility), standardized tests of spelling and receptive vocabulary, and two experimental tasks focusing on spelling generation and spelling identification using pseudo-words matched on phonotactic probability. Results: Using Spearman's correlation, significant relationships were found between the number of pseudo-words spelled and identified correctly. Further examination using a Wilcoxon Signed-Ranks test revealed a significant difference between list presentation type for the percentage of correctly spelled pseudo-words during the spelling generation task, but not for percentage of correctly identified words in the spelling identification task. A significantly greater percentage of consonant and vowel sounds were produced during the spelling generation task when individual sounds of the words were provided; however, there was no difference in performance during the identification task. Conclusions: Results suggest that speech perception has a strong influence than speech production in the development of spelling skills for children with CCN who do and do not use AAC. Further research is required on how to best teach spelling while taking advantage of perceptual abilities.